Inferior Vena Cava Agenesis: an incidental diagnosis during electrophysiological study - Ferreira Filho, Sérgio Ferreira de; Agnese, Marco Antonio Vinciprova Dall; Leiria, Tiago Luiz Luz; Schäfer, Luísa Rohr; Kruse, Marcelo; Lima, Gustavo Glotz de (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Inferior Vena Cava Agenesis (IVCA) is a rare congenital anomaly occurring in 0.0005% to 1% of the general population. Although often asymptomatic, IVCA significantly increases the risk of serious thromboembolic events, including chronic venous insufficiency, pulmonary thromboembolism, and deep vein thrombosis (DVT). This study investigates the incidence and clinical implications of IVCA discovered incidentally during electrophysiological studies (EPS) at the Instituto de Cardiologia do Rio Grande do Sul over the past 27 years. A cross-sectional review of 13,194 EPS reports from January 1997 to July 2024 identified 12 cases (0.09%) of incidentally diagnosed IVCA. Of the patients in question, 66.7% were female, with a mean age of 44.6 years. One patient had a history of complex heart disease, and arrhythmia induction was a potential outcome in 66.7% of cases. Atrioventricular node reentry tachycardia (AVNRT) was the most common arrhythmia observed. Catheterization of the right heart chambers via the azygos system was feasible in 83.3% of cases. One patient experienced deep vein thrombosis and pulmonary thromboembolism post-procedure, which was managed with anticoagulation. The study highlights the importance of recognizing IVCA during EPS as it can impact catheterization techniques and procedural outcomes. Although IVCA is a rare occurrence, it should be considered as a potential cause of difficulties encountered during catheterization procedures, and alternative access methods should be prepared. This awareness is crucial for preventing complications and ensuring effective treatment of cardiac arrhythmias.